Implementasi Lean Six Sigma Berbasis DMAIC dalam Perancangan Strategi Kaizen untuk Peningkatan Kualitas Produksi Packing Chocogranule - Citra Ramadhanti, Lifia; Effendi, Rizal; Edhiargo Toyosito, Rakay (Dinasti Research, 2026)
This research discusses the high level of defective packaging in the WIP Chocogranule production process at PT TES, which leads to waste and reduced production efficiency. The main problem identified is non-standard packaging cuts. The study aims to determine the dominant factors causing defects and to design continuous improvement strategies using a DMAIC-based Lean Six Sigma approach combined with Kaizen, the seven quality tools, FMEA, and the 5W+1H method. The research focuses on five waste-causing factors: machines, materials, methods, manpower, and the environment. Primary data were obtained from observations of packaging defects using a sample of 100 pieces per day, while secondary data consisted of inner cellophane variance before and after improvements. The analysis results indicate that the dominant defect is non-standard packaging cuts, accounting for 73.13% of defects, with an average of 1.95 defects per 100 samples. The initial DPMO value was 8,889 with a sigma level of 3.87. The improvement phase produced six main corrective actions, including machine modifications, process standardization, changes in packing flow, increasing eyemark width, and operator training. The implementation of these improvements successfully reduced cellophane waste from 2.67% to below the company’s KPI target of 0.67%, with the DPMO value decreasing to 2,222 and the sigma level increasing to 4.34. This study demonstrates the effectiveness of Lean Six Sigma and Kaizen in improving quality and efficiency in the production process.